2017
DOI: 10.1113/jp272837
|View full text |Cite
|
Sign up to set email alerts
|

Visceral and somatic pain modalities reveal NaV1.7‐independent visceral nociceptive pathways

Abstract: Voltage-gated sodium channel Na 1.7 is required for acute and inflammatory pain in mice and humans but its significance for visceral pain is unknown. Here we examine the role of Na 1.7 in visceral pain processing and the development of referred hyperalgesia using a conditional nociceptor-specific Na 1.7 knockout mouse (Na 1.7 ) and selective small-molecule Na 1.7 antagonist PF-5198007. Na 1.7 mice showed normal nociceptive behaviours in response to intracolonic application of either capsaicin or mustard oil, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 61 publications
5
70
0
1
Order By: Relevance
“…NaV 1.7 appears to be involved in chronic pain mechanisms as upregulation of NaV channels has been detected after disc injury in murine models; moreover, the administration of anti‐NaV 1.7 antibodies decreased CGRP expression in mice after lumbar disc injury (Nojima et al, ). Conversely, the role of this channel in visceral pain remains unknown; in fact, Nav 1.7 seems not to be required for visceral pain processing, and a very recent study advocates that pharmacological block of NaV 1.7 alone in the viscera may be insufficient in targeting chronic visceral pain (Hockley et al, ). NaV 1.8 is involved in different adaptive and neuroplasticity‐related mechanisms on which light has been shed with NaV 1.8 gene knock‐out models: different investigations detected a marked hyperalgesia after nociceptive stimulation in mice (Dong, Sun, Lu, Wang, & Wu, ); also, if a Chronic Constriction Injury (CCI) was provoked in mice, mRNA alteration and protein rearrangement were observed in cells (Wang, Wang, et al, ).…”
Section: Gdnf and Voltage Gated Sodium Channelsmentioning
confidence: 99%
“…NaV 1.7 appears to be involved in chronic pain mechanisms as upregulation of NaV channels has been detected after disc injury in murine models; moreover, the administration of anti‐NaV 1.7 antibodies decreased CGRP expression in mice after lumbar disc injury (Nojima et al, ). Conversely, the role of this channel in visceral pain remains unknown; in fact, Nav 1.7 seems not to be required for visceral pain processing, and a very recent study advocates that pharmacological block of NaV 1.7 alone in the viscera may be insufficient in targeting chronic visceral pain (Hockley et al, ). NaV 1.8 is involved in different adaptive and neuroplasticity‐related mechanisms on which light has been shed with NaV 1.8 gene knock‐out models: different investigations detected a marked hyperalgesia after nociceptive stimulation in mice (Dong, Sun, Lu, Wang, & Wu, ); also, if a Chronic Constriction Injury (CCI) was provoked in mice, mRNA alteration and protein rearrangement were observed in cells (Wang, Wang, et al, ).…”
Section: Gdnf and Voltage Gated Sodium Channelsmentioning
confidence: 99%
“…antagonist (PF-5198007) demonstrated no significant impact on visceral sensory afferent activity in response to painful stimuli. 44 This same investigation also demonstrated no impact of Na V 1.7 antagonism on afferent neuronal activity associated with excised human appendices exposed to significant intraluminal distension. In other human studies, however, biopsy samples from patients diagnosed with idiopathic rectal hypersensitivity and paroxysmal extreme pain disorder (PEPD) (aka familial rectal pain) demonstrated that Na V 1.7positive nerve fibers were observed more frequently in these patients compared to healthy controls.…”
Section: Na V 17mentioning
confidence: 77%
“…However, the large majority of intestinally innervating afferent nerves demonstrate elements that are most characteristic for Na V 1.8 (eg, high threshold, slowly inactivating, TTX‐resistant) . Evidence for all nine VGSC isoforms has been demonstrated at the level of mRNA transcript and/or protein expression in sensory afferent neurons and other cell types associated with gut nociception . However, some of these isoforms (eg, Na V 1.2, Na V 1.4) have, as of yet, no experimentally delineated role in visceral pain perception and so will not be discussed further.…”
Section: The Influence Of Voltage‐gated Sodium Channels (Vgscs) On Gamentioning
confidence: 99%
See 2 more Smart Citations